Identification of TIMING OF CAB EXPRESSION 1 as a temperature-sensitive negative regulator of tuberization in potato. (20th July 2019) - Morris, Wayne L; Ducreux, Laurence J M; Morris, Jennifer; Campbell, Raymond; Usman, Muhammad; Hedley, Pete E; Prat, Salomé; Taylor, Mark A
Abstract : TIMING OF CAB EXPRESSION 1 (StTOC1) is a temperature-responsive negative regulator of tuberization. This clock protein interacts directly with the StSP6A tuberization signal and suppresses its positive feed-forward regulation in stolons. Abstract: For many potato cultivars, tuber yield is optimal at average daytime temperatures in the range 14–22 °C. Above this range, tuber yield is reduced for most cultivars. We previously reported that moderately elevated temperature increases steady-state expression of the core circadian clock gene TIMING OF CAB EXPRESSION 1 ( StTOC1 ) in developing tubers, whereas expression of the StSP6A tuberization signal is reduced, along with tuber yield. In this study we provide evidence that StTOC1 links environmental signalling with potato tuberization by suppressing StSP6A autoactivation in the stolons. We show that transgenic lines silenced in StTOC1 expression exhibit enhanced StSP6A transcript levels and changes in gene expression in developing tubers that are indicative of an elevated sink strength. Nodal cuttings of StTOC1 antisense lines displayed increased tuber yields at moderately elevated temperatures, whereas tuber yield and StSP6A expression were reduced in StTOC1 overexpressor lines. Here we identify a number of StTOC1 binding partners and demonstrate that suppression of StSP6A expression is independent of StTOC1 complex formation with the potato homolog StPIF3. Down-regulation of StTOC1 thus provides a strategy to mitigate the effects of elevated temperature on tuber yield.